SOSIALISASI GURU DIGITAL DAN KAMPANYE ETIKA DIGITAL DI SMA N 2 LOBALAIN - Khatrin Juliani Taku Neno; Selfiana T. M. Ndapalawa (Pengabdian Masyarakat Ilmu Pendidikan, 2026)
This Community Service Program aimed to improve students’ awareness of ethical and responsible digital technology use through digital teacher socialization and a digital ethics campaign at SMA Negeri 2 Lobalain. The program employed socialization activities, interactive discussions, and digital ethics campaigns. The results showed increased students’ understanding of ethical communication, digital privacy, and critical attitudes toward digital information. This activity contributed to fostering a positive digital culture within the school environment.